KUALITAS PELAYANAN PEMBUATAN SURAT IZIN USAHA PERDAGANGAN (SIUP) DI KOTA PONTIANAK - Viranty Firmanila E42009083 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The purpose of this study is to describe and analyze the quality of business trading license service (SIUP) in Pontianak City. The title of this study was appointed by the problems that occur in the service of making business trading license which giving rise to complaints from the public due to the lack of maximum of the service. This research uses descriptive study with a qualitative approach. The study subjects were employees of Badan Perizinan Terpadu (BP2T) Pontianak City that involved in the making of business trading license (SIUP) service and also people who managed the making of business trading license (SIUP) service. The result of this study is that the overall quality of SIUP service process which performed by BP2T Pontianak City is not good enough. Dimensions of service quality related to the process of making SIUP which are tangibility, realibility, responsiveness, assurance, and emphaty  must be improved to provide maximum service quality.  The results recommend Badan Perizinan Terpadu (BP2T) Pontianak City to improve the quality of services such as adding physical facilities, equipment, personnels, discipline and reliability as well as managing the complaint in accordance with procedures. Keywords : Quality, Service, tangibility, realibility, responsiveness, assurance, emphaty.